PENGARUH FAKTOR-FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PENGEMBANGAN INDUSTRI KELAPA DI KABUPATEN INDRAGIRI HILIR - Nusyirwan Ry; Djaimi Bakce; Jumatri Yusri (UIR Press, 2017)
Indragiri Hilir District has 515,200 hectares of local coconut land with production of 418,200 tons (Statistic Board, 2015), but the area of land and its production is always decreasing. The decline of the area is caused by land damage, land conversion, the number of coconut plants that are old and dead and so affect to the need of raw materials for the development of the coconut industry in generating the number and type of product diversification. This research is conducted to analyze the internal and external factors that were influences to the development of local coconut industry which aims to know the internal and external factors in the development of coconut industry in Indragiri Hilir district. The result of the analysis showed that the internal factors that become the strength and impact on the development of the coconut industry are the large area of coconut plant that is large enough, the availability of a large workforce and already has a large scale coconut processing industry; while the weakness factor is the age of coconut plants is quite old, coconut farmersgenerally use local seeds, decreased coconut productivity and the limited number and type of diversification of coconut derived products. External factors that become opportunities for the development of the coconut industry is the high demand for coconut products and derivatives in the export market, coconut derivative products can still be developed and supported by local government and related agencies while external factors are a threat to the coconut industry development of coconut plantation damage due to sea water intrusion and high investment concerns in competing countries against the coconut industry.